O conceito de cultura no contexto da internacionalização: discursos no âmbito do Programa Idiomas Sem Fronteiras - Duarte, Talita Valcanover (2020)
The main theme of this paper is the relation between of culture and language teaching. This paper is part of the research line “Language in the Social Context” of the Letters Post-Graduate Program (PPGL) of the Federal University of Santa Maria (UFSM), and it was developed with the support of the Coordination for the Improvement of Higher Education Personnel – Brazil (CAPES) – Financial Code 001. Due to the need for combating discourses about culture which compare social groups and nations to overvalue some to the detriment of others, and the duty to combat stereotypes and debate the diversity and multiplicity as the current world condition where no one is better or worse than any one, but different, this research aims to investigate the discourses about the concept of culture in the Language without Boarders Program (IsF). Currently, the IsF program is a great incentive for the internationalization of Brazilian universities through the provision of online and face-to-face English courses and teaching residency for language teachers. According to Motta-Roth (2006), within the area of Applied Linguistics, there is no monolithic concept of culture with a single, cohesive and coherent discourse, probably because it is an interdisciplinary area that dialogues with other areas. Thus, the concepts of culture considered are: culture with “small c” or “discursive genre"; culture with “capital C” and "high culture”. The research is based on the qualitative analysis of perceptions about the concept of culture within the Program, based on two data sets: 1) Course Programs offered by the IsF program and 2) questionnaires with teachers in teaching residence and students who participated of the course “Cultural Differences” in UFSM. The results indicate the occurrence of the three concepts of culture, with an emphasis on “big C” and “small c” or culture as “discursive genre”. The Course Programs pointed out with greater emphasis on "big C", while the teachers and students had more balanced speeches about the concepts. Therefore, it can be said that the speeches about culture at the IsF are directed towards more current concepts about this theme.